Hyperglycemic hyperosmolar state in children: a case series - Leni Lukman; I Made Darma Yuda; I Made Arimbawa (Intisari Sains Medis, 2022)
Background: Hyperglycemic hyperosmolar state (HHS) is a life-threatening rare acute complication of diabetes mellitus (DM). The condition should be distinguished from diabetic ketoacidosis (DKA) as the management differs significantly. HHS is classically associated with type 2 DM, but it has been increasingly reported in type I DM as well. The literature regarding HHS in children is still sparse. The management of HHS in children is extrapolated from the adult study. Cases: The first case was male 5 years old, and the second case was female 15 years old. Both cases were typed 1 DM patient. The first case was newly diagnosed. Both of the patients came with general weakness, mild dehydration, overly high blood sugar, normal blood pH, hypocalcemia, glucosuria and only mild ketonuria. In the second case develop, both patients were rehydrated, given insulin and discharged in 7-10 days without any sequelae. Conclusion: These case series emphasize the importance of recognizing HHS and differ it from DKA. These two cases prove that HHS is increasingly reported in children with clinical symptoms resembling DKA. It is also proven that with early diagnosis and correct management, children with HHS can be discharged home without any sequelae.